Catalytic Selective Oxidation of Primary and Secondary Alcohols Using Nonheme [Iron(III)(Pyridine‐Containing Ligand)] Complexes. Issue 42 (28th October 2020) - Panza, Nicola; di Biase, Armando; Rizzato, Silvia; Gallo, Emma; Tseberlidis, Giorgio; Caselli, Alessandro
Abstract : The selective oxidation of different primary and secondary alcohols to carbonyl compounds by hydrogen peroxide was found to be catalyzed in conversion ranging from good to excellent by an iron(III) complex of a pyridine‐containing macrocyclic ligand (Pc‐L), without the need of any additive. The choice of the counteranion (Cl, Br, OTf) appeared to be of fundamental importance and the best results in terms of selectivity (up to 99 %) and conversion (up to 98 %) were obtained using the well‐characterized [Fe(III)(Br)2 (Pc‐L)]Br complex, 4c . Magnetic moments in solid‐state, also confirmed in solution ([D6 ]DMSO) by Evans NMR method, were calculated and point out to an iron metal center in the high spin state of 5/2. The crystal structure shows that the iron(III) center is coordinated by the four nitrogen atoms of the macrocycle and two bromide anions to form a distorted octahedral coordination environment. The catalytic oxidation of benzyl alcohol in acetonitrile was found occurring with better conversions and selectivities than in other solvents. The reaction proved to be quite general, tolerating aromatic and aliphatic alcohols, although very low yields were obtained for terminal aliphatic alcohols. Preliminary mechanistic studies are in agreement with a catalytic cycle promoted by a high‐spin iron complex. Abstract : Selective oxidation of several primary and secondary alcohols to carbonyl compounds by hydrogen peroxide are performed with [Fe(III)(Pc‐L)] catalysts (Pc‐L = pyridine‐based 12‐membered tetraaza‐macrocyclic ligands) in the absence of any additive. Preliminary mechanistic studies are in agreement with a catalytic cycle promoted by a high‐spin iron complex.